2006
DOI: 10.1590/s0066-782x2006001900002
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos hormônios tireoidianos nas síndromes coronarianas agudas

Abstract: Objective: To describe thyroid hormone profile in patients with acute coronary syndromes (ACS), divided into two groups: 1) unstable angina and/or non-ST-segment elevation acute myocardial infarction (UA/NSTEMI); 2) ST-segment elevation acute myocardial infarction (STEMI), as well as in patients that progressed or not to death, according to the groups.Methods: Seventy ACS patients admitted to the coronary care unit of the Hospital dos Servidores do Estado, Rio de Janeiro, were prospectively studied. Blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This pattern of thyroid hormone alterations was described in several scenarios of acute or chronic illness ( 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ). In addition, there is a significant correlation between altered thyroid hormone levels and the severity and duration of disease ( 9 , 10 , 11 , 12 , 17 , 18 , 19 , 20 ). Several studies found an association between low T3 and disease severity.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…This pattern of thyroid hormone alterations was described in several scenarios of acute or chronic illness ( 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ). In addition, there is a significant correlation between altered thyroid hormone levels and the severity and duration of disease ( 9 , 10 , 11 , 12 , 17 , 18 , 19 , 20 ). Several studies found an association between low T3 and disease severity.…”
Section: Introductionmentioning
confidence: 78%
“…T3 levels both on time 0 (admission) or time 1 had a good accuracy to predict short- and long-term mortality, comparable to other prognostic validated clinical scores. Accordingly, it was previously suggested that adding T3 to other severity scores ( 9 , 29 , 41 ). Moreover, serum T3 is an easy, reliable, and applicable test that can, individually or in combination with the other severity scores, increase the sensitivity to highlight those patients with a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The thyroid hormone profile tends to have a controversial impact on the incidence and prognosis of ACS across the literature. For instance, Pimentel et al suggest that euthyroid sick syndrome (ESS) indicates a poorer overall prognosis for ACS patients [ 15 ], although ESS is likely a consequence of ACS rather than a cause [ 16 ]. A similar conclusion was reached by Lamprou et al [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported about NTIS in subjects with AMI [ 3 , 6 , 7 , 10 ]. In AMI condition, decrease of free T3 and increase of reverse T3 have been documented [ 15 , 16 ]. In animal models, Ojamaa et al [ 17 ] showed that low T3 levels fell within 1 week of AMI and remained > 40% lower than those in controls 4 weeks after AMI.…”
Section: Discussionmentioning
confidence: 99%